Porous media transport phenomena - Civan, Faruk (Wiley, 2011)
"This book covers the mass, momentum, and energy conservation equations, and their applications in engineered and natural porous media for general applications. This book is an important text for graduate courses in various disciplines involving fluids in porous materials and a useful reference book. It provides a multi-disciplinary approach to transport in porous media. This book covers general porous media applications including chapters on the effect of temperature and particle migration and provides emphasis in energy resources development. The material is presented in a uniform format with consistent SI units"--